MSH2 knock-down shows CTG repeat stability and concomitant upstream demethylation at the DMPK locus in myotonic dystrophy type 1 human embryonic stem cells. (26th November 2020) - Franck, Silvie; Barbé, Lise; Ardui, Simon; De Vlaeminck, Yannick; Allemeersch, Joke; Dziedzicka, Dominika; Spits, Claudia; Vanroye, Fien; Hilven, Pierre; Duqué, Geoffrey; Vermeesch, Joris R; Gheldof, Alexander; et al.
Abstract: Myotonic dystrophy type 1 (DM1) is caused by expansion of a CTG repeat in the DMPK gene, where expansion size and somatic mosaicism correlates with disease severity and age of onset. While it is known that the mismatch repair protein MSH2 contributes to the unstable nature of the repeat, its role on other disease-related features, such as CpG methylation upstream of the repeat, is unknown. In this study, we investigated the effect of an MSH2 knock-down (MSH2KD) on both CTG repeat dynamics and CpG methylation pattern in human embryonic stem cells (hESC) carrying the DM1 mutation. Repeat size in MSH2 wild-type (MSH2WT) and MSH2KD DM1 hESC was determined by PacBio sequencing and CpG methylation by bisulfite massive parallel sequencing. We found stabilization of the CTG repeat concurrent with a gradual loss of methylation upstream of the repeat in MSH2KD cells, while the repeat continued to expand and upstream methylation remained unchanged in MSH2WT control lines. Repeat instability was re-established and biased towards expansions upon MSH2 transgenic re-expression in MSH2KD lines while upstream methylation was not consistently re-established. We hypothesize that the hypermethylation at the mutant DM1 locus is promoted by the MMR machinery and sustained by a constant DNA repair response, establishing a potential mechanistic link between CTG repeat instability and upstream CpG methylation. Our work represents a first step towards understanding how epigenetic alterations and repair pathways connect and contribute to the DM1 pathology.